Faktor-Faktor yang Mempengaruhi Permintaan Rumah Bersubsidi diKota Banjarbaru - Naura, Emylda; Maulina, Dessy (PPJP ULM, 2025)
This study aims to determine the effect of house prices, per capita income, and interest rates simultaneously and partially that affect the demand for subsidized housing in Banjarbaru City. This research uses multiple linear regression research methods with quantitative secondary data with a time series of 2010-2022. The results stated that simultaneously, all independent variables had a significant effect on the demand for subsidized houses in Banjarbaru City. Partially, price has a positive and significant effect, while interest rates have a negative and significant effect on the demand for subsidized houses in Banjarbaru city. While per capita income is negative and has no significant effect on the demand for subsidized housing in Banjarbaru city.